Rare bird documentation form for Peregrine Falcon along Cedar River in Waterloo, 1980 - Myers, Robert K.et al (1980)
Rare bird documentation form for a Peregrine Falcon along Cedar River in Waterloo in Black Hawk County, IA on September 19, 1980. Epson - sheet feed